Regional productivity differences in the European Union - Theoretical predictions and empirical evidence - Kurt Geppert; Martin Gornig; Andreas Stephan (European Regional Science Association (ERSA), 2003)
The analysis of regional income and productivity differences in the European Union (EU) has some tradition. The theoretical framework of most empirical studies on these subjects is the neoclassical growth model. Thus, research has focussed on convergence of income and productivity among EU regions. While spatial clustering is an issue in a number of studies, geography is rarely taken into account. This paper takes an explicitly spatial perspective, so we are able to look at an alternative theoretical approach, the New Economic Geography (NEG). Our regional classification is a modified version of the NUTS2 level. We use the degree of agglomeration and the geographical location (core vs. periphery) as geographical indicators. This allows for the empirical evaluation of some of the ideas of NEG regarding the pattern and development of regional productivity differences of EU regions. The analysis covers the period from 1982 to 2000. We develop a two-stage estimation strategy. Using panel data analysis in the first stage we estimate region-specific effects on productivity and its dynamics in terms of production and employment growth. In the second stage we apply Analysis of Covariance in order to explain those region-specific effects through other time-invariant factors and to estimate the impact of these factors on productivity. Our results indicate a strong significance of region-specific factors for productivity differences in the EU. The geographical indicators are significant but their impact appears to be rather limited. While the estimated parameters of the categorial spatial variables are consistent with predictions of the NEG, unobserved heterogenity at the national level is much more important. State-specific effects can explain a major part of variation in regional productivity. This implies that the regional pattern of productivity in the EU still is largely determined by national "productivity regimes". Regarding the productivity dynamics in the EU, we find a tendency towards convergence. This is in line with most other empirical studies on this subject. However the decrease of regional productivity differences is the result of two opposite processes: There is convergence of production but divergence of employment. Again national factors appear to dominate. We find that the dynamics of regional development in terms of output and employment growth are strongly determined by state-specific effects and these effects are varying significantly over time. A tentative interpretation of our results is that the economic development of regions within the EU can not be easily explained by either neoclassical theory or NEG. The reduction in regional productivity differences appears to be formed to a large extent by factors at the national level. Examples are the downsizing of low productivity agriculture in southern european countries or the boost in part-time employment in the Netherlands during the eighties. Further empirical research will have to establish whether the national component in regional development is attenuating and a European pattern of productivty growth is emerging.
Keywords: 330